1985
DOI: 10.2135/cropsci1985.0011183x002500020004x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Honey Bee Foraging Activity and Pollination Efficacy for Male‐Sterile Cotton1

Abstract: The effectiveness of honey bees, Apis mellifera L., as pollinators of male‐sterile cotton, Gossypium hirsutum L., was evaluated using 649 colonies located adjacent to 53 ha of cotton grown on Pullman clay loam (fine, mixed, thermic Torrertic Paleustoll) near Plainview, TX. The planting pattern used was 2A (male‐sterile seed parent): 2B (male‐fertile maintainer) rows throughout. Colonies were evaluated for population, brood, and weight changes. Observers recorded bee visits to flowers of both A‐line and B‐line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
1
14
1
Order By: Relevance
“…Cott on (Gossypium hirsutum L., Malvaceae) is a valuable plant from which fl oral and extrafl oral nectaries are collected by honeybees for honey production. However, honeybees seldom visit and obtain pollen from cott on plants (25,26). Cott on pollen is covered with sticky material (27) which makes its grooming from the body of bees painstakingly hard and it explains the avoidance of cott on pollen by honeybees (28).…”
Section: Pollen Content Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cott on (Gossypium hirsutum L., Malvaceae) is a valuable plant from which fl oral and extrafl oral nectaries are collected by honeybees for honey production. However, honeybees seldom visit and obtain pollen from cott on plants (25,26). Cott on pollen is covered with sticky material (27) which makes its grooming from the body of bees painstakingly hard and it explains the avoidance of cott on pollen by honeybees (28).…”
Section: Pollen Content Of the Samplesmentioning
confidence: 99%
“…Cott on pollen is covered with sticky material (27) which makes its grooming from the body of bees painstakingly hard and it explains the avoidance of cott on pollen by honeybees (28). In another study, the repellency of cott on is att ributed to the gossypol, which is a dimeric sesquiterpenoid (25).…”
Section: Pollen Content Of the Samplesmentioning
confidence: 99%
“…Heavy dew also effected foraging activity adversely in morning. Waller et al (1985) found that the peak foraging activity of bees on R line flowers was before noon in hybrid seed production plots of cotton.The peak foraging activity of honeybees on CMS flowers of B. napus was recorded at 1400 h. It should be mentioned here that these flowers provide only nectar. The present observations are in line with several previous observations (Meyerhoff 1954 Kubisova et al 1986;1987) The hours of the day appeared to play a significant role in attracting bees for foraging as the nectar production or its concentration in male as well as in female line flowers and also the pollen dehiscence in male parent line are related with day hours or indirectly the prevailing temperature, humidity, light intensity and other environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…Bumble bees (Bombus), honey bees (Apis), Anthophora, Melissodes and Halictus bees and Scolia wasps are important pollinators in some areas (McGregor, 1976;Free, 1993;Delaplane and Mayer, 2000). Apis mellifera can be an important pollinator, but it does not prefer Gossypium pollen (McGregor, 1976;Eisikowitch and Loper, 1984;Vaissière et al, 1984;Waller et al, 1985;Loper, 1986;Vaissière, 1991;Vaissière and Vinson, 1994;Danka, 2005;Van Deynze et al, 2005). In using insecticides to manage the crop, mitigation measures are taken to preserve the pollinator populations, for example by not applying insecticides during the effective period of flowering (Delattre, 1992;Bourland et al, 2001;Sekloka et al, 2007).…”
Section: Floral Biology Pollination and Development Of Seedsmentioning
confidence: 99%